Transformasi Sampah Anorganik menjadi Produk Bernilai Guna - Rusdiyatun Nur Annisa; Nadilla Lisa Safitri; Ivana Azaria Widy; Sardjito Eko Windarso; Ghulamin Khalim Subagiyo (Lembaga Pengembangan Kinerja Dosen, 2025)
The issue of inorganic waste such as plastic and used paper in industrial environments remains an important issue that affects the cleanliness and aesthetics of work areas. PT Pertamina Patra Niaga Fuel Terminal Rewulu faces challenges in managing non-hazardous solid waste due to limited sorting systems and waste transportation frequency. This Community Service activity aims to improve workers' understanding and skills through socialization and training in making ecobricks as a solution for utilizing inorganic waste. The methods used include pre-activity stages, socialization and hands-on practice, and evaluation through pre-tests and post-tests. The results of the activity showed a significant increase in participants' knowledge after the training, proving the effectiveness of interactive methods in strengthening understanding of the 3R (Reduce, Reuse, Recycle) concept. In addition to reducing waste volume, this activity also fostered awareness and participation among workers in creating a clean and sustainable work environment. The results of this community service are important as a first step in building a culture of independent waste management in industrial environments and can be replicated in other locations with a similar approach. Keywords: Implementation of Pancasila values, bullying prevention, character education, primary school, SDN 1 Jatisela, school environment, student behaviour.